2020
DOI: 10.3390/jcm9041117
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Learning via Deep Neural Networks for Implant Fixture System Classification Using Periapical Radiographs

Abstract: In the absence of accurate medical records, it is critical to correctly classify implant fixture systems using periapical radiographs to provide accurate diagnoses and treatments to patients or to respond to complications. The purpose of this study was to evaluate whether deep neural networks can identify four different types of implants on intraoral radiographs. In this study, images of 801 patients who underwent periapical radiographs between 2005 and 2019 at Yonsei University Dental Hospital were used. Imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 34 publications
5
81
0
Order By: Relevance
“…The same was found to be true for the classification of dental implants using CNNs [13]. From our study, we found that CNNs using panoramas lead to results comparable to the diagnostic accuracy of dental implant classification by CNNs using periapical radiographic images [13]. These results will contribute to the accuracy of CNN classification diagnoses by increasing the number of images used via preprocessing.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The same was found to be true for the classification of dental implants using CNNs [13]. From our study, we found that CNNs using panoramas lead to results comparable to the diagnostic accuracy of dental implant classification by CNNs using periapical radiographic images [13]. These results will contribute to the accuracy of CNN classification diagnoses by increasing the number of images used via preprocessing.…”
Section: Discussionsupporting
confidence: 77%
“…Because panoramic radiographs have different distortions depending on the region to be photographed, periapical radiographic images have generally been used for diagnosis, whereas CNNs have been used for tooth-related classifications and diagnoses [32,33]. The same was found to be true for the classification of dental implants using CNNs [13]. From our study, we found that CNNs using panoramas lead to results comparable to the diagnostic accuracy of dental implant classification by CNNs using periapical radiographic images [13].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In particular, as newly developed DCNN models and algorithms are continuously adopted and coupled with the area of implant dentistry, it may be an important adjunct for diagnosis, treatment, and prognosis assessments [ 26 ]. Recent DCNN-related studies confirmed that various types of DIs with different shapes, lengths, or dimensions can be effectively detected and classified using panoramic and periapical images [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of machine learning, model-based transfer learning has become a popular method in the field of computer vision because it allows for accurate modeling and takes less time. It is also effective in applying learned features from large datasets to small datasets to raise their accuracy and performance [26]. With transfer learning, the model to be trained does not start from scratch, but from the patterns that have been learned when solving various problems.…”
Section: Introductionmentioning
confidence: 99%